The Association of Stage 1 Hypertension, Defined by the 2017 ACC/AHA Guidelines, With Cardiovascular Events Among Rural Women in Liaoning Province, China - Wu, Jiake; Duan, Weili; Jiao, Yundi; Liu, SiTong; Zheng, LiQiang; Sun, YingXian; Sun, ZhaoQing (Frontiers in Cardiovascular Medicine, 2021)
Background: The recent American College of Cardiology/American Heart Association (ACC/AHA) guidelines redefined blood pressure levels 130-139/80-89 mmHg as stage 1 hypertension. However, the association of stage 1 hypertension with cardiovascular disease (CVD) and its age-specific differences among the rural women in Liaoning province remains unclear. It needs to be quantified in considering guideline adoption in China. Methods: In total, 19374 women aged ≥35 years with complete data and no cardiovascular disease at baseline were followed in a rural community-based prospective cohort study of Liaoning province, China. Follow-up for the new cases of CVD was conducted from the end of the baseline survey to the end of the third follow-up survey (January 1, 2008-December 31, 2017). Adjusted Cox proportional hazards models were applied to estimate the Hazard Ratios (HR) and 95% Confidence Intervals (CI) with the normal blood pressure as a reference. Results: During the median follow-up period of 12.5 years, 1,419 subjects suffered all-cause death, 748 developed CVD, 1,224 participants suffered stroke and 241 had Myocardial Infarction (MI). Compared with normal BP, Stage 1 hypertension had a HR (95% CI) of 1.694 (1.202–2.387) in CVD mortality, 1.575 (1.244–1.994) in the incidence of stroke. The results obtained that the risk of CVD mortality and incidence of stroke was significantly associated with stage 1 hypertension in rural women aged ≥45 years after adjusting for other potential factors. However, in participants aged 35-44 years, stage 1 hypertension was not associated with an increased risk of cardiovascular disease. Conclusions: The newly defined stage 1 hypertension is associated with an increased risk of CVD mortality and also incidence of stroke in the rural women aged ≥45 years population of Liaoning province. This study can be a good reference for health policy makers and clinicians workers to make evidence-based decisions towards lowering burden of cardiovascular disease more efficient, timely measures on prevention and control of stage 1 hypertension in China.